Enhancing the efficacy of 5-HT uptake inhibitors in the treatment of attention deficit hyperactivity disorder. (December 2019) - Riley, Timothy B.; Overton, Paul G.
Abstract: Attention Deficit Hyperactivity Disorder (ADHD) is one of the most common childhood behavioural disorders, the frontline treatments for which are drugs with abuse potential. As a consequence, there is an urgent need to develop non addictive drug treatments with equivalent efficacy. Preclinical evidence suggests that selective serotonin uptake inhibitors (SSRIs) are likely to be effective in ADHD, however clinical reports suggest that SSRIs are of limited therapeutic value for the treatment of ADHD. We propose that this disconnect can be explained by the pattern of drug administration in existing clinical trials (administration for short periods of time, or intermittently) leading to inadequate control of the autoregulatory processes which control 5-HT release, most notably at the level of inhibitory 5-HT1A somatodendritic autoreceptors. These autoreceptors reduce the firing rate of 5-HT neurons (limiting release) unless they are desensitised by a long term, frequent pattern of drug administration. As such, we argue that the participants in earlier trials were not administered SSRIs in a manner which realises any potential benefits of targeting 5-HT in the pharmacotherapy of ADHD. In light of this, we hypothesise that there may be under-researched potential to exploit 5-HT transmission therapeutically in ADHD, either through changing the administration regime, or by pharmacological means. Recent pharmacological research has successfully potentiated the effects of SSRIs in acute animal preparations by antagonising inhibitory 5-HT1A autoreceptors prior to the administration of the SSRI fluoxetine. We suggest that combination therapies linking SSRIs and 5-HT1A antagonists are a potential way forward in the development of efficacious non-addictive pharmacotherapies for ADHD.